SCIDOT-22. INTRACEREBROVENTRICULAR DELIVERY OF TUMOR-HOMING CYTOTOXIC HUMAN INDUCED NEURAL STEM CELLS FOR TREATMENT OF BRAIN METASTASES. (11th November 2019) - Jiang, Wulin; Mercer-Smith, Alison; Bago, Juli; Khagi, Simon; Anders, Carey; Hingtgen, Shawn
Abstract: INTRODUCTION: Non-small cell lung cancer (NSCLC) and breast cancer are the most common cancers that metastasize to the brain. New therapies are needed to target and eradicate metastases. We have developed genetically-engineered induced neural stem cells (hiNSCs) derived from human fibroblasts that selectively home to tumors and release the cytotoxic protein TRAIL. Building on these results, we explored the efficacy of hiNSC therapy delivered via intracerebroventricular (ICV) injections for the treatment of metastatic foci in the brain for the first time. METHODS: We performed in vitro efficacy and migration assays in conjunction with in vivo studies to determine the migration, persistence, and efficacy of therapeutic hiNSCs against H460 NSCLC and triple-negative breast cancer MB231-Br tumors in the brain. Following the establishment of tumors in the brains of nude mice, hiNSCs were injected directly into the tumor or the ventricle contralateral to the tumor. The migration and persistence of hiNSCs were investigated by following the bioluminescence of the hiNSCs. The therapeutic efficacy of the hiNSCs was determined by following the bioluminescence of the tumor. RESULTS/ CONCLUSION: Co-culture results demonstrated that hiNSC therapy reduced the viability of H460 and MB231-Br up to 75% and 99.8% respectively compared to non-treated controls. In vitro migration assays showed significant directional migration toward both lung and breast cancer cells within 4 days. ICV-administered hiNSC serial imaging shows that cells persisted for >1 week in the brain. Fluorescent analysis of tissue sections showed that hiNSCs co-localized with lateral and contralateral tumors within 7 days. Using H460 and MB231-Br models, kinetic tracking of intracranial tumor volumes showed intratumoral or ICV-injected therapeutic hiNSCs suppressed the growth rate of brain tumors by 31-fold and 3-fold, respectively. This work demonstrates for the first time that we can effectively deliver personalized cytotoxic tumor-homing cells through the ventricles to target brain metastases.